Oxymatrine inhibited the progression of renal cell carcinoma by increasing TOR1AIP1 expression - Yan, Xuechuan; Zhao, Kai; Zhang, Zongliang; Yin, Xinbao; Yang, Han; Jiang, Zaiqing; He, Tianzhen; Wang, Ke (Frontiers in Pharmacology, 2025)
AimsThe extract of Radix sophorae tonkinensis, known as oxymatrine (OMT), demonstrates anticancer properties. This investigation explored the influence of oxymatrine on renal cell carcinoma (RCC) and elucidated the associated molecular mechanisms, both in vitro and in vivo.MethodsRNA-seq was used to evaluate target genes regulated by OMT. The potential target gene TOR1AIP1 was identified, and the expression of TOR1AIP1 was analyzed in RCC cell lines (Caki-1 and 786-O cells) after treatment with OMT. Further functional assays, including in vitro proliferation, migration, and invasion experiments, were performed. Additionally, overexpression experiments were used to confirm the role of TOR1AIP1 in RCC. In vivo assays using a nude mouse model were conducted to evaluate the effect of OMT on tumor growth.ResultsWe identified TOR1AIP1 as the potential target gene ofOMT. Among the tested compounds, OMT significantly increased the expression of TOR1AIP1 in RCC cells. OMT inhibited RCC progression, including cell proliferation, migration, and invasion, by upregulating TOR1AIP1. Mechanistically, overexpression of TOR1AIP1 in RCC cells markedly inactivated the JNK signaling pathway and suppressed RCC development. In vivo, OMT treatment significantly inhibited tumor growth, consistent with the in vitro findings.ConclusionOur findings demonstrate that OMT suppresses RCC progression by increasing the expression of TOR1AIP1 and inactivating the JNK signaling pathway. These findings support TOR1AIP1 as a mechanistic mediator of OMT’s antitumor effects in RCC models and provide a rationale for further evaluation in physiologically relevant in vivo systems and with formal pharmacokinetic and toxicity studies.